Isolation of Lawsonia intracellularis specific single-chain Fv antibody fragments from phage display library - Dezorzová-Tomanová, Katarína; Molinková, Dobromila; Pekarová, Mária; Celer, Vladimír; Smola, Jiří (Research in Veterinary Science, 2007)
Single-chain antibodies (scFv) exhibiting specific binding to Lawsonia intracellularis were isolated from a phagemid library expressing scFvs molecules on the surface of filamentous bacteriophages. For scFv selection whole bacterial cells were used and individual clones were tested in ELISA test. The total of seven unique clones with different fingerprint profiles was isolated. All clones were able to bind specifically in immunofluorescence assay. This is the first report of species specific recombinant antibodies against L. intracellularis.
Keywords: Lawsonia (bakterie); protilátky bakteriální; financování organizované; Antibodies, Bacterial; peptidová knihovna; Antibody Specificity; Lawsonia Bacteria; Financing, Organized; Humans; Peptide Library; specificita protilátek; lidé; Immunoglobulin Variable Region; variabilní oblast imunoglobulinu